Heart Rate Asymmetry Analysis During Head-Up Tilt Test in Healthy Men - Pawłowski, Rafał; Buszko, Katarzyna; Newton, Julia L.; Kujawski, Sławomir; Zalewski, Paweł (Frontiers in Physiology, 2021)
The purpose of this study is assessment of cardiovascular system response to orthostatic stress in a group of 133 healthy men using Heart Rate Asymmetry methods. Heart Rate Asymmetry (HRA) is a feature of variability in human heart rate which is dependent upon external and internal body conditions. The initial phases of Head Up Tilt Test (HUTT), namely supine and tilt, were chosen as the external body affecting factors. Various calculation methods of HRA, such as Porta’s Index (PI), Guzik’s Index (GI) and its variance based components, were used to assess the Heart Rate Variability (HRV) and its asymmetry. We compared 5 minute ECG recordings from both supine and tilt phases of HUT test. Short-term HRA was observed in 54.1% of men in supine phase and 65.4% of men in tilt phase. The study revealed significant increase of GI (from 0.50 to 0.52, p < 0.001) in the tilt phase as well as significant changes in HRV descriptors between HUTT phases. Our results showed that the variability of human heart rate and its asymmetry are sensitive to orthostatic stress. The study of short-term HRA is a potential additional tool to increase sensitivity in conditions where HUTT is a diagnostic tool, such as vasovagal syncope.